Dok-1 negatively regulates platelet integrin αIIbβ3 outside-in signalling and inhibits thrombosis in mice - Niki, Masaru; Nayak, Manasa K.; Jin, Hong; Bhasin, Neha; Plow, Edward F.; Pandolfi, Pier Paolo; Rothman, Paul B.; Chauhan, Anil K.; Lentz, Steven R. (Thrombosis and Haemostasis, 2016)
Adaptor proteins play a critical role in the assembly of signalling complexes after engagement of platelet receptors by agonists such as collagen, ADP and thrombin. Recently, using proteomics, the Dok (downstream of tyrosine kinase) adapter proteins were identified in human and mouse platelets. In vitro studies suggest that Dok-1 binds to platelet integrin β3, but the underlying effects of Dok-1 on αIIbβ3 signalling, platelet activation and thrombosis remain to be elucidated. In the present study, using Dok-1-deficient (Dok-1-/-) mice, we determined the phenotypic role of Dok-1 in αIIbβ3 signalling. We found that platelets from Dok-1-/- mice displayed normal aggregation, activation of αIIβ3 (assessed by binding of JON/A), P-selectin surface expression (assessed by anti-CD62P), and soluble fibrinogen binding. These findings indicate that Dok-1 does not affect “inside-out” platelet signalling. Compared with platelets from wild-type (WT) mice, platelets from Dok-1-/- mice exhibited increased clot retraction (p < 0.05 vs WT), increased PLCγ2 phosphorylation, and enhanced spreading on fibrinogen after thrombin stimulation (p < 0.01 vs WT), demonstrating that Dok-1 negatively regulates αIIbβ3 “outside-in” signalling. Finally, we found that Dok-1-/- mice exhibited significantly shortened bleeding times and accelerated carotid artery thrombosis in response to photochemical injury (p < 0.05 vs WT mice). We conclude that Dok-1 modulates thrombosis and haemostasis by negatively regulating αIIbβ3 outside-in signalling.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Fibrinogen; haemostasis; integrin; platelets; thrombin; thrombosis